Testicular size in our male population - Dimitrovski, Chedomir; Krstevska, Brankica; Sadikario, Samuel; Plasheski, Tosho; SHubeska Stratrova, Slavica (Македонско лекарско друштво = Macedonian medical association, 1998)
Testicular size was measured in 800 healthy males ages 7 through 42. Testicular volumes were estimated by Prader's orchidometer. At chronological age 7-11 years, the normal mean testicular volume (MTV) ranged from 1.30 to 4.82cm³, and in 11-13 year old children 7.46 to 8.95cm³. It could mean that in our male population, puberty commences at 11-13 years of age. After 17 years of age, MTV was relatively stable and ranged from 18.25 to ±6,27cm³. Orchidometry could be useful in anthropological investigations and especially in routine clinical practice for evaluating the development of male puberty and andrological disorders.
Големина на тестисите кај нашата машка популација
Keywords: testis; orchidometry; male puberty; andrology